2022
DOI: 10.3390/nu14040858
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Hemoglobin Concentrations and Birth Weight, Low Birth Weight (LBW), and Small for Gestational Age (SGA): Findings from a Prospective Study in Northwest China

Abstract: Birth weight and related outcomes have profound influences on life cycle health, but the effect of maternal hemoglobin concentration during pregnancy on birth weight is still unclear. This study aims to reveal the associations between maternal hemoglobin concentrations in different trimesters of pregnancy and neonatal birth weight, LBW, and SGA. This was a prospective study based on a cluster-randomized controlled trial conducted from July 2015 to December 2019 in rural areas of Northwest China. Information on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 48 publications
(73 reference statements)
2
14
1
4
Order By: Relevance
“…Finally, maternal anaemia had significant effects of on the newborn birth weight. This study’s findings are similar to those study reported in China 61 , India 40 , Brazil 62 , Nepal 63 Colombia 64 , Eastern Ethiopia 65 , and Southern Punjab, Asia 66 . This could be because of intrauterine growth restriction.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, maternal anaemia had significant effects of on the newborn birth weight. This study’s findings are similar to those study reported in China 61 , India 40 , Brazil 62 , Nepal 63 Colombia 64 , Eastern Ethiopia 65 , and Southern Punjab, Asia 66 . This could be because of intrauterine growth restriction.…”
Section: Discussionsupporting
confidence: 91%
“…Relatively low maternal Hb in the third trimester usually reflects changes in plasma volume rather than poor maternal nutrition or adaptation [43]. However, a recent prospective study from Northwest China showed an inverted U-shaped association between maternal Hb in the third trimester and neonatal birth weight [23], and a significant positive correlation between maternal Hb in the third trimester and birth weight was reported in another study [44]. This may be because, even in the third trimester, maternal Hb in different periods reflects different conditions of the intrauterine environment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a study found a faint U-shaped relationship between maternal Hb concentration at ≤20 weeks of gestational age and risk of neonatal adverse outcomes (including preterm deliveries, SGA) [22]. However, another study from Northwest China showed a U-shaped relationship between Hb concentration in the third trimester and the risk of SGA/LBW, as well as an inverted U-shaped relationship between maternal Hb and neonatal birth weight [23]. Meanwhile, several studies reported the association between Hb reduction and birth outcomes [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of a high global anemia rate in pregnant women, iron deficiency accounts for 20–50% of anemia occurrences ( 27 , 28 ). Comparative evidence suggests that iron supplementation improves hematologic biomarkers such as hemoglobin and ferritin ( 7 , 29 ). However, there are also studies reported that routine iron supplementation in non-anemic gestational woman has no benefit on pregnancy outcomes, and caution is advised against Fe supplementation already ( 8 ).…”
Section: Discussionmentioning
confidence: 99%